Effects of EPS density on blast mitigation performance in underground protective structures. (June 2022) - Ichino, Hiroyoshi; Beppu, Masuhiro; Williamson, Eric B; Haraguchi, Nozomu
Highlights: Shock absorbing effects of EPS in a layered blast mitigation system are examined. There is an optimum EPS density in a mitigation system for decreasing blast pressure. An equation that estimates the optimum EPS density is proposed. Blast pressure account for the effects of EPS density is formularized. Abstract: Explosions due to terrorist attacks or accidents can cause severe damage to critical infrastructure. To protect important facilities from blast damage, they can be constructed belowground. Further, an explosion mitigation layer consisting of soil and foam material can be used to provide additional protection. In this study, the effects of expanded polystyrene foam (EPS) density on blast mitigation system effectiveness were investigated experimentally. From the test results, an equation that estimates the optimum EPS density to most effectively reduce peak blast pressure is proposed. Moreover, equations for estimating the peak pressure and scaled impulse at the bottom of a mitigation system, which account for the effects of EPS density, have also been proposed.